The Perceptions and Experiences of Mobile Health Technology by Older People in Guangzhou, China: A Qualitative Study - Tu, Jiong; Shen, Manxuan; Zhong, Jiudi; Yuan, Gang; Chen, Miaohong (Frontiers in Public Health, 2021)
The study explores older people's perceptions and experiences with mobile technology adoption in hospitals. Twenty nine older people were interviewed at a tertiary hospital in Guangzhou from June to December 2020. All the interviews were analyzed using thematic analysis. Older people are a diversified group. Various factors impact their readiness for technology use, including their educational level, age, past experiences, living arrangements, etc. The older people in this study in general expressed a great concern about using the new health technology and many encountered barriers to its successful adoption. Yet, the barriers and difficulties that they encountered are embedded in a changed social context in China. The findings above provide insights into the adoption of health technology, and tailored measures to facilitate older people's technology adoption are suggested.